STABILITY ANALYSYS OF DYNAMIC MODEL OF DEPOSITS AND LOANS BETWEEN THREE BANK USING SPIRAL OPTIMIZATION - Oyko Noer Wijayanti, Belva
Banks are financial intermediary institution that stand between savers and borrowers. Nowadays, study about financial stability of banking is important to observe the financial condition in the future. In this final project, dynamics system models of deposits and loans between three banks were constructed using Lotka Volterra Model with adaptation of logistic models. The model is implemented into data of commercial banks in Indonesia. Numerical parameter estimation is carried out by Spiral Optimization Algorithm (SOA). The result shows that from 48 constructed models, there are 27 models that have a satisfactory solution. Furthermore, from 27 models given that 7 models are not converging to their fixed point in a long time and other 20 models that the deposits and loans volume will be stable at their equilibrium points.